Pemanfaatan Tanah Subur Melalui Pendampingan Budidaya Sayuran Secara Organik - Apriatin, Lia; Kamelia, Lia (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2021)
Cisauheun is a beautiful environment where the majority of the population works as farmers. The vast agricultural area and fertile soil make many farmers use their land to grow rice, but in Cisauheun cultivation to grow vegetables is still low, this is due to low knowledge and skills in cultivating vegetables. Therefore, community empowerment this time is one of the focuses with the implementation of an empowerment program through vegetable cultivation training in the Cisauheun environment. The method used in this activity is in the form of planting training with the help of organic fertilizer. We aim to improve the knowledge and skills of the cisauheun community in cultivating vegetables well while helping to provide opportunities for the community to make the vegetables they grow as additional income for their families. In the process of implementing the training as well as direct practice, the training on vegetable cultivation went smoothly and there were not many obstacles. The results we got from the cultivation of these vegetables were the planting of seeds of garlic, shallots, sausin, kale and chilies in an empty land called "greeunhose cisauheun" . The vegetable plants will later be maintained by a group of housewives who collaborate with mosque youth.